(untitled) (Proceedings of the International Conference on Education, 2025)
This study aims to examine the relationship between digital literacy and civic engagement of 150 Gen Zs. The findings showed a moderate correlation (r = 0.340, p < 0.001), indicating a contribution of digital literacy to civic participation of 11.5%. Meanwhile, the results of interviews with 18 Civics lecturers illustrate three obstacles to Gen Z’s involvement in pub lik issues, namely dominated by social media algorithms that emphasize entertainment content rather than policy discussions, a rigid Civics learning approach that has not responded to digital dynamics, and gaps in access and inequality in using digital technology. Not a few lecturers suggested strengthening the project-based learning model based on the value of Pancasila as the state ideology. Integration of critical algorithm literacy in Civics learning is needed. These findings provide an important contribution to the pedagogical reform agenda in education. Citizenship. Especially strengthening the capacity for participation of the younger generation in the digital era. There are limitations in scope, sampling, and test subjects in this study, which only focuses on the Indonesian context. This recommendation aligns with achieving Sustainable Development Goals (SDGs) related to quality education and resilient institutions